Une approche paysagère des effets de 30 années de développement de jardins partagés - Morgane Robert (Développement Durable et Territoires)
This article proposes to develop a landscape approach to the socio-ecological dynamics of shared gardens applied to a case study: the Grand Parc in Bordeaux. The historical involvement of the Scop SaluTerre in the design of these gardens constitutes a support for the analysis of regulation or social exclusion phenomena, as well as public action effects on landscape. For this, we will develop the hypothesis that the institutional recovery of shared gardens – unlike their emergence directly within resident communities – imposes by various mechanisms many landscape forms and practices, potentially excluding certain uses and social categories.